Destilação: a obtenção do óleo essencial de mastruz - GOULART, Estéfany Batista; GUIMARÃES, Letícia Silva; OLIVEIRA, Victória Inácio Carreto de (165, 2025)
A palavra "destilação" tem origem no latim destillatio, vem do verbo de-stillare, que significa "gotejar". O processo de destilação consiste na separação de substância líquida através da sua evaporação e condensação. Um exemplo pode ser observado quando o vapor de água se deposita em gotas de água destilada numa superfície fria, neste caso a tampa de uma panela. Na destilação, o calor atua como o agente separador, pois o vapor gerado apresenta uma composição distinta da mistura original. O método de destilação é amplamente utilizado na indústria química. O Mastruz foi escolhido por ser uma planta popularmente conhecida por suas propriedades terapêuticas como ação antimicrobiana, antifúngica e anti-inflamatória. A obtenção do óleo essencial proporcionou uma vivência prática da técnica de destilação, evidenciando a relevância do entendimento químico na valorização de recursos naturais. Os resultados alcançados destacam o potencial do óleo essencial da planta mastruz para aplicação em diversas áreas, como saúde, cosméticos e produtos naturais, sublinhando a importância da química na criação de soluções sustentáveis e eficazes. The word "distillation" comes from the Latin word destillatio, and comes from the verb de-stillare, which means "to drip". This process consists of separating a liquid substance through its evaporation and condensation. An example can be seen when water vapor settles in drops of distilled water on a cold surface, in this case the lid of a pan. In distillation, heat acts as the separating agent, since the vapor generated has a different composition from the original mixture. The distillation method is widely used in the chemical industry, such as in the production of rectified alcohol from a fermentation mixture. It is a process that involves a change in physical state, in which a substance, initially in a liquid state, is heated until it reaches boiling point. By supplying heat to a liquid mixture, we promote its partial evaporation, and then we obtain two phases, one liquid and the other vapor, which have different compositions. The difference in composition of the two phases results from the difference in volatility of the various components of the initial mixture. The greater this difference in volatility, the greater the difference in composition between the liquid and vapor phases. There are several types of distillation, with the most common and widely used in industry being simple and fractional distillation. However, there is also vacuum distillation and steam distillation. Simple distillation allows two components to be separated efficiently.
Distillation: obtaining essential oil from mastruz
Keywords: Bioprocessos; Produção Industrial